Effects of magnetic nanoparticles dysprosium oxide (Dy2O3) addition on electrical properties of (Bi,Pb)-2223 high TC superconductors / Nurul Raihan Mohd Suib - Mohd Suib, Nurul Raihan (2010)
In this study, co-precipitation technique has been performed in preparation of Bi1.6Pb0.4Sr2Ca2Cu3O10 ceramic superconductor. In order to change the electrical properties of the superconductor powder, magnetic nanoparticles Dy2O3 were added with nominal composition ranging from x=0 to x=0.10 wt% at different sintering time. The ultrafine superconductor powder produced by co-precipitation method has increased the diffusion reaction and shortened the heat treatment procedure for the sample preparation. These lead to better superconducting properties as compared to the samples prepared by conventional solid state technique where its diffusion reaction require s a high temperature and long sintering hour, it is laborious , time intensive and contaminated products may be occurred. Co-precipitation method has proved it high TC at 102 K when sintered for 24 hours. Absolutely, this time taken probably unachieved at same sintering time to solid state technique probably it’s taken more longer time to have the same TC. From this study the resistivity measurement has been done for all samples, and showed that Tc(R=0) from 100-109 K and Tc-onset 108-117 K. The TC achieved showed the high TC when it is more than 100 K. From XRD analysis, samples showed that the grain and formation of phase is more dominated by Bi-2223 phase rather than Bi-2212 when varied of wt% addition magnetic nanoparticles Dy2O3 to all samples. Results from XRD shows the peak of DY2O3 was not detected. It implied that the magnetic nanoparticles of DY2O3 was incorporated in the crystalline structure, However in EDX shows the distribution of magnetic nanoparticles DY2O3 so it showed the existed of DY2O3 in samples. From SEM analysis, showed also the large flaky of (Bi,Pb)-2223 structure was randomly distributed. The effect of magnetic nanoparticles DY2O3 addition on superconducting material s will alter the electron pairing mechanism and affected the flux pinning strength. With prolonged the sintering time, it shows an improvement in superconducting electrical properties. The optimum sintering time is 48 hours, where the highest JC was obtained at 18.82±0.86 A/cm2 at 30 K.